Designing a Prototype for Abdullah bin Saud School Webpage - Abdulaziz, Albelaihy Abdullah (2011)
Content management systems for the educational environments presents the suitable solution for indicating and managing students, teachers, and staff activities based technology. This study focus on the different issues in managing and determining the school and users performance in Abdullah Bin Saud School. The school lacking to provide the suitable managing services for its contents based on online services. Thus, this study was found to design, develop, and evaluate a website application for Abdullah Bin Saud School (ABSS). SDLC Prototyping Model was used in this study to design, develop, and evaluate the proposed system. As well, PHP and MYSQL were adopted for building the ABSS website. After all, an evaluation was conducted with 30 students to indicate their perceived ease of use and usefulness towards the use of ABSS. The results show that participants were found ABSS to be ease and useful to use.